2014
DOI: 10.1007/s10103-014-1563-y
|View full text |Cite
|
Sign up to set email alerts
|

Do laser/LED phototherapies influence the outcome of the repair of surgical bone defects grafted with biphasic synthetic microgranular HA + β-tricalcium phosphate? A Raman spectroscopy study

Abstract: The treatment of bone loss is difficult. Many techniques are proposed to improve repair, including biomaterials and, recently, phototherapies. This work studied bone mineralization by Raman spectroscopy assessing intensities of Raman peaks of both inorganic (∼ 960, ∼ 1,070 cm(-1)) and organic (∼ 1,454 cm(-1)) contents in animal model. Six groups were studied: clot, laser, light-emitting diode (LED), biomaterial (HA + β-tricalcium phosphate), laser + biomaterial, and LED + biomaterial. Defects at right tibia we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Another study has indicated that LED application might increase new bone formation area, number of osteoblasts/osteoclasts, and vessels on rats subjected to orthopedic maxillary expansion [58]. Further researches have also demonstrated LED ability on promoting angiogenesis [59][60], and as an important adjunctive factor involved in the improvement of dentoalveolar osteogenesis [61].…”
Section: Introductionmentioning
confidence: 99%
“…Another study has indicated that LED application might increase new bone formation area, number of osteoblasts/osteoclasts, and vessels on rats subjected to orthopedic maxillary expansion [58]. Further researches have also demonstrated LED ability on promoting angiogenesis [59][60], and as an important adjunctive factor involved in the improvement of dentoalveolar osteogenesis [61].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, photobiomodulation has shown promising results in stimulating cell proliferation, especially fibroblasts, macrophages and lymphocytes. It also promotes angiogenesis and synthesis of collagen [21][22][23][24]. Specifically, the use of low-level laser therapy (LLLT) for wound healing, nerve injury repair, as well as the reduction of inflammation and pain, was tested shortly after the invention of lasers [25].…”
Section: Introductionmentioning
confidence: 99%
“…Current investigations are challenged daily by the need to recover bone loss due to surgical procedures, trauma or pathological conditions. Several techniques for the repair of bone defects have been studied with the use of bone grafts and photobioengineering [1][2][3]. The use of bone grafts for repairing the maxillofacial deformities is a relatively common procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Laser light has been used for accelerating bone repair in autologous bone grafts [1], dental implants [14] and different types of bone defects [15]. Low-intensity light therapy, ordinarily referred to to as photombiomodulation (PBM) by light in the far-red to near-infrared (NIR) region of the spectrum (630-1000 nm), stimulates several cellular functions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation